History and memory in African-American culture - Fabre, Geneviève; O'Meally, Robert G., 1948- (OUP E-Books., 1994)
The relation between history and memory has become an object of increasing attention among historians and literary critics. Through a team of leading scholars, this volume offers a complex picture of the dynamic ways in which an African-American historical identity constantly invents and transmits itself in books, art, performance, and oral documents.